The Transformation of Islamic Education in the Era of Digital Globalization: The Strategic Role of Educational Technology in Strengthening Islamic Values - Emha Dzia’ul Haq; Sri Adiningsih (Institut Agama Islam Persis Bandung, 2025)
This study aims to comprehensively analyze the strategic role of educational technology in strengthening Islamic values amidst the rapid current of digital globalization. Employing a qualitative approach through a critical literature review, this study explores the theoretical concepts, practical implementations, and sociocultural implications of technology integration within Islamic education. The analysis reveals that the transformation of Islamic education demands epistemological reconstruction and curricular innovation capable of harmonizing classical Islamic scholarly traditions with 21st-century global competencies. The utilization of advanced technologies, particularly Artificial Intelligence (AI), must strictly be positioned as a wasilah (instrumental means) regulated within the framework of cyber ethics and the principles of maqāṣid al-syarī‘ah, to mitigate disinformation and fortify students' critical reasoning. The success of this transformation heavily relies on multisectoral synergy, the application of pedagogical innovations such as Project-Based Learning (PBL), and the continuous capacity building of educators' digital literacy. This study concludes the necessity of a comprehensive institutional strategy to cultivate an adaptive learning ecosystem that shapes a Muslim generation characterized by both noble morality and digital intelligence